Social impact of volunteer tourism towards host community in Perhentian Island, Terengganu - Nur Hidayah Zulkifli, 1985-, author; Norhazliza Abd. Halim, supervisor; Fakulti Alam Bina (2015)
Thesis (Sarjana Sains (Perancangan Pelancongan)) - Universiti Teknologi Malaysia, 2015